161 LIFESTYLE OUTCOME STUDY FOLLOWING BODY CONTOURING IN MASSIVE WEIGHT LOSS PATIENTS. Issue 1 (1st January 2007) - Davis, M.; Gabriel, A.; Shores, J.; Carter, J.; Gupta, S.
Abstract : Introduction: Body contouring operations following massive weight loss are being performed at an exponentially increasing rate. Although highly effective for reshaping the body, these operations are associated with a high cost incurred by the patient. Traditionally, body contouring procedures have been considered an aesthetic procedure. However, due to disproportionate excess skin distribution, massive weight loss (MWL) patients often have a functional disability, which adversely affects their quality of life. Whereas some insurance companies are reimbursing for these procedures, most continue to consider body contouring as strictly cosmetic and ineligible as a covered benefit. The purpose of our study was to analyze the outcome benefit in patients undergoing body contouring following massive weight loss. Methods: This single-center, multisurgeon body contouring outcome study was designed to assess the overall outcome and life-changing events that took place following the surgery. Twenty-five consecutive patients with an average age of 38 years (range 18-65 years) who underwent body contouring surgery were followed for 8 months. Postoperative evaluations were standardized and quantified with a validated series of short questionnaires (30 questions) that assessed measures in an objective and subjective manner. Questionnaires were designed to address specific lifestyle benefits attributed to body contouring. Results: Of 25 patients who completed the survey, 84% were female. The mean BMI was 45. The majority of patients experienced positive lifestyle outcomes as a result of having had the procedure: 100% reported increases confidence and noted an increase in self-esteem; 100% felt more comfortable in clothes. A number of patients had changed careers and increased their annual income. In addition, 100% of patients indicated that their overall health had improved due to their ability to be more involved in society, improved ability to ambulate, and exercise. Discussion: These data provide an assessment of some outcomes associated with weight loss procedures commonly performed in the United States. Although most health care insurance companies are hesitant to recognize body contouring as an essential procedure for MWL patients, we believe that our study demonstrates both objective and subjective improvements in quality of life and health. Body contouring in MWL patients represents the final stage in the surgical transformation of obese patients. There is little doubt that these procedures are invaluable and should be made more readily available to those patients who cannot afford the out-of-pocket expense.